Advantages Of Decision Trees Using Data Mining In Indian Retail Industry - Ranjan, Jayanthi; Agarwal, Ruchi (Journal of Knowledge Management Practice, 2010)
Indian Retail industry has emerged as one of the most dynamic and fast paced industries with several players entering the market. The data that retail industry collect about their customers is one of the greatest assets of it. Data mining (DM) helps in extracting the buried valuable information within the vast amount of data. The decision trees using DM could make a significant difference to the way in which a retail industry run their business, and interact with their current and prospective customers. The derived information can be utilized in predicting, forecasting and estimating the important business decisions, which can help in giving a retailer the competitive edge over their competitors. The paper demonstrates the advantages of decision trees using DM in Indian retail industry with the help of an empirical study.
Keywords: knowledge management; Data mining; Decision trees; Retail industry; Customers